National technology and industrial base integration : how to overcome barriers and capitalize on cooperation - McCormick, Rhys; Cohen, Samantha; Hunter, Andrew P.; Sanders, Gregory; Mooney, Samuel; Herschlag, Daniel (Center for Strategic & International Studies, 2018)
In light of Section 881 of the National Defense Authorization Act for Fiscal Year 2017, which expanded the legal definition of the National Technology and Industrial Base (NTIB) to include the United Kingdom and Australia, this report informs NTIB partners on barriers and opportunities for effective integration. The expansion of the NTIB is based on the principle that defense trade between the United States and its closest allies enables a host of benefits, including increased access to innovation, economies of scale, and interoperability. In order to reap the greatest benefits of a new era of NTIB, this report uses the lessons learned from study of the present state of integration to identify areas of opportunity for policy reforms and greater cooperation.